SARS-CoV-2 Vaccines Based on the Spike Glycoprotein and Implications of New Viral Variants - Martínez-Flores, Daniel; Zepeda-Cervantes, Jesús; Cruz-Reséndiz, Adolfo; Aguirre-Sampieri, Sergio; Sampieri, Alicia; Vaca, Luis (Frontiers in Immunology, 2021)
Coronavirus Disease 19 (COVID-19) is a disease originating in the province of Wuhan, China in 2019, it is caused by the betacoronavirus severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), whose infection in humans causes mild or severe clinical manifestations that mainly affect the respiratory system. So far, the COVID-19 has caused more than 2 million deaths worldwide. SARS-CoV-2 contain the Spike (S) glycoprotein on its surface, which is the main target for vaccine development because antibodies directed against this protein can neutralize the infection. Companies and academic institutions have developed vaccines based on the S glycoprotein, as well as its antigenic domains and epitopes, demonstrating its effectiveness, receiving approvals for its emergency use in several countries. However, the emergence of new SARS-CoV-2 variants casts doubt on continued effectiveness and with it the end of the pandemic. Here, we review the different types of vaccines designed and developed against SARS-CoV-2, we make a detailed description of the structural characteristics of antigens derived from SARS-CoV-2, depending on whether they are based on the complete S glycoprotein, its antigenic domains such as the receptor-binding domain (RBD) or short epitopes within S. We also review and discuss the effectiveness of these vaccines in the face of the emergence of new SARS-CoV-2 variants and possible strategies that can help end the COVID-19 pandemic.